Injury patterns of non-fatal accidents related to ice hockey, an analysis of 7 years of admission to a Level-1 Emergency Centre in Switzerland - Gilardi, V.; Kotsaris, S.; Exadaktylos, A.; Klukowska-Rötzler, J. (PLOS ONE, 2023)
Objective This study was carried out to identify the frequency and types of injuries in adult ice hockey, in order to better understand injury patterns and identify potential areas for injury prevention. Methods We conducted a retrospective database review of acute injuries reported in ice hockey in patients presenting to a Level-1 adult Emergency Centre in Switzerland. Patients between January 1, 2013 and December 31, 2019 and over 16 years of age were identified in our computerised patient database. Each consultation was reviewed to derive information on demographics, playing level and the features of the injury, including location, type, mechanism and consequences. Different age groups were compared, as were amateur and professional players. A statistical analysis was performed. Results A total of 230 patients were identified. The most common diagnoses were fracture (28.3%), contusion/abrasion (23.9%), laceration (12.6%) and concussion (10.4%). The most commonly affected body parts were the face (31.3%), the shoulder/clavicle (13.0%) and the head (12.2%). Most lesions were caused by player-player contact (37.4%), contact with the puck (24.3%) and falls (10.9%). In comparison to the younger cohorts, patients >36 years of age more frequently suffered injuries caused by falls, (p < 0.001) and were less frequently injured by player-player contact (p = 0.01813). In amateur players, significantly more injuries were caused by stick contact (OR 0, 95% CI (0.00-0.83), p = 0.02) and surgery was more rarely performed (OR 2.35, 95% CI 0.98-5.46, p = 0.04). Conclusions Injuries continue to play a major role in ice hockey, especially in the face and due to player-player contact. Future investigations should focus on player-player contact and possible effective preventive measures. Players must be encouraged to employ face protection and to wear a mouth guard at all times.